Hubungan Pemberian Asi Ekslusif dengan Tingkat Stunting pada Balita Usia 1-3 Tahun - Arifah, Siti; Sudariyekti, Arian Wirani (Journal of Telenursing (JOTING), 2024)
The aim of this research is to find out whether there is a relationship between exclusive breastfeeding and the level of stunting in toddlers aged 1-3 years. This research uses a quantitative cross-sectional correlation approach. The sample method in this study was simple random sampling of 93 respondents who had stunted toddlers aged 1-3 years from two sub-districts in the Surakarta area in 2023. The instruments used in this study were height measurements and a demographic questionnaire. The research results were analyzed using frequency and Spearman distribution statistical tests. The results showed that there was a relationship between exclusive breastfeeding and the level of stunting with a value of 0.015 (p=<0.05). Conclusion: There is a relationship between exclusive breastfeeding and the level of stunting in toddlers aged 1-3 years. Keywords: Exclusive Breastfeeding, Toddlers, Stunting